The effect of flap thickness on the hydrodynamic performance of an oscillating wave surge converter - James Julian; Rasya Aulia Nathania Nisa; Fitri Wahyuni; Riki Hendra Purba; Fathin Muhammad Madhudhu; Elvi Armadani (Jurnal Polimesin, 2025)
With the growing demand for energy and the need to transition to renewable sources, ocean wave energy presents great potential. The Oscillating Wave Surge Converter (OWSC) is a promising technology due to its nearshore applicability, structural simplicity, and robust design. This study systematically investigates the effect of flap thickness on the dynamic performance of a hinge-mounted OWSC using the Boundary Element Method (BEM).Â Â  The research models the hydrodynamic interactions and analyzes the effects of three different flap thicknesses on key metrics, including maximum angle deviation, angular velocity, torque, and power capture. The results indicate that all flap variations demonstrate stable oscillatory movement, but greater flap thickness reduces the maximum angle deviation due to increased inertia and hydrostatic pressure. A resonant peak was observed for all thicknesses at a wave period of 1.3 seconds, where energy transfer was maximized. At this frequency, the thickest flap achieved the highest efficiency (78.94%), followed by the intermediate (77.50%) and thinnest (70.77%) variations. The findings suggest that while flap thickness influences efficiency, the primary factor for maximizing energy capture is the alignment of the wave period with the device's natural frequency.